Eletrofiação de compósitos com matriz polimérica de PEDOT:PSS - Costa, Eduardo Lima (2019)
Electrospinning is a manufacturing polymer technique based on a controlled electrostatic field, producing fibers on nanometric scale with high superficial area and porosity. This technique allows a variety composite or charge deposition on a polymeric matrix, improving its intrinsic properties, such as electric, mechanical, thermal and optical properties. Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) is a polymeric blend with good electric conductivity, thermal stability, chemical, and oxidant, optical transparency and plasticity, properties that allow the polymeric blend to be used to obtain thin films, as other structures such as nanofibers and nanowires obtained by electrospinning technique. In a nanometric scale, materials based on conjugated polymers present a wide range of properties, allowing different post-treatment, increasing its applications, due intrinsic properties or due association with other materials. Silver nanowires (AgNW) are interesting due its properties such as optical transparency, and thermal and electric conductivity, being used on organic composites to increase those properties on organic matrix for more applications. One of those applications is Polymeric Solar Cells (PSC), lending between two layers of the dispositive, acting as an interface of the anode material and the electron donor material. In this paper, electrospinning and spin-coating techniques are analyzed for thin films production and optimization of electric, optic and morphologic properties of PEDOT:SS/AgNW composites obtain by electrospinning and spin-coating techniques, supported by Design of Experiments (DOE). Thin films produced has 40 nm of thickness, electric conductivity of 150 S/cm, and transparency of 92% for visible light.